Potential roles of nitrate and nitrite in nitric oxide metabolism in the eye - Ji Won Park (Nature Portfolio, 2020)
Abstract Nitric oxide (NO) signaling has been studied in the eye, including in the pathophysiology of some eye diseases. While NO production by nitric oxide synthase (NOS) enzymes in the eye has been characterized, the more recently described pathways of NO generation by nitrate (NO3 −) and nitrite (NO2 −) ions reduction has received much less attention. To elucidate the potential roles of these pathways, we analyzed nitrate and nitrite levels in components of the eye and lacrimal glands, primarily in porcine samples. Nitrate and nitrite levels were higher in cornea than in other eye parts, while lens contained the least amounts. Lacrimal glands exhibited much higher levels of both ions compared to other organs, such as liver and skeletal muscle, and even to salivary glands which are known to concentrate these ions. Western blotting showed expression of sialin, a known nitrate transporter, in the lacrimal glands and other eye components, and also xanthine oxidoreductase, a nitrate and nitrite reductase, in cornea and sclera. Cornea and sclera homogenates possessed a measurable amount of nitrate reduction activity. These results suggest that nitrate ions are concentrated in the lacrimal glands by sialin and can be secreted into eye components via tears and then reduced to nitrite and NO, thereby being an important source of NO in the eye.